(untitled) (Revista de Crítica Literaria Latinoamericana, 2017)
This work studies the strategic facet of American nature in the chronicle La Florida del Inca, written by Inca Garcilaso de la Vega. Thus, departing from a brief introduction about the notion of landscape in the Chronicles of Indies, I will approach the strategic function of landscape analizing the chronicler’s descriptions, which offer a pragmatic view of nature in that territory. In this way, I will present examples of how conquerors turn each one of the environment components such as flora, fauna, and climate into useful elements to complete the Spanish expedition. Once I have analyzed this strategic function of the American nature in La Florida del Inca, I will compare it with those descriptions given by Alvar Núñez Cabeza de Vaca in Naufragios, a chronicle that does also describes this North American area.